How to prioritize as a citizen of the universe - Colter, Jackson T., author; Kasser, Jeff, advisor; Archie, Andre, committee member; Heineman, Kristin, committee member (Colorado State University. Libraries, 2024)
Stoicism has gained a bit of popularity in certain circles recently, and much of this popularity revolves around the way that Stoicism enables and guides moral progress on an individual level, regardless of the circumstances. However, Stoic ethics also features an element of cosmopolitanism - essentially, other-oriented ethical principles that an ideal Stoic would follow. These principles tell us that we are all members of a common rational community, with every agent in the rationally organized universe being a member of this community. Naturally, the human lifespan is not long enough to equally address every rational being in the universe, so some sort of prioritization is required. However, Stoics place two requirements on our actions. We must ground our actions in knowledge, and both Marcus Aurelius and Epictetus directly advise us to avoid unnecessary actions. These requirements combined with the other-oriented moral principles lead Stoics to a state of moral paralysis - where the actions that seem to be morally required of them are epistemically unjustified. This paralysis needs to be solved if Stoicism is to serve as a meaningful system of other-oriented ethics. Fortunately, an account of expertise is given in a piece of secondary literature by Simon Shogry which, combined with later Stoic insights, serves to alleviate this paralysis.
Keywords: epistemology; Stoicism; stoic; cosmopolitan